2011
DOI: 10.1177/1352458511433063
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3-like 1 plasma levels are increased in patients with progressive forms of multiple sclerosis

Abstract: These findings point to a role of CHI3L1 in patients with progressive forms of MS, particularly in those with PPMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 16 publications
(24 reference statements)
3
41
1
1
Order By: Relevance
“…Similarly, the minor rs4950928 G allele played a protective role in children and young adults with asthma [31]. Besides, the rs4950928 was also associated with primary progressive multiple sclerosis, with the increased CHI3L1 levels [32] implying that the minor G allele of rs4950928 conferred protection against central nervous system diseases, including AD. On the other hand, rs10399931, as a variant SNP (< 200 bp) at the transcription initiation site of CHI3L1 [33], was reported to be an effective marker for predicting the risk and severity of asthma in the Taiwanese population [34], which indicated that the T allele of rs10399931 C>T may be a risk factor for diseases.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, the minor rs4950928 G allele played a protective role in children and young adults with asthma [31]. Besides, the rs4950928 was also associated with primary progressive multiple sclerosis, with the increased CHI3L1 levels [32] implying that the minor G allele of rs4950928 conferred protection against central nervous system diseases, including AD. On the other hand, rs10399931, as a variant SNP (< 200 bp) at the transcription initiation site of CHI3L1 [33], was reported to be an effective marker for predicting the risk and severity of asthma in the Taiwanese population [34], which indicated that the T allele of rs10399931 C>T may be a risk factor for diseases.…”
Section: Discussionmentioning
confidence: 93%
“…The optic coherent tomography provides information on axonal damage and can be used to monitor it. Potential prognostic markers are immunoglobulins M (IgM) [10] and neurofilaments in CSF [11,12], antimyelin [13], and chitinase-3-like protein 1 (CH3L1) [14] in blood and CSF [15]. These markers have to be validated before their use in clinical practice [9].…”
Section: Clinical Evaluation Of Musmentioning
confidence: 99%
“…Some of the differentially regulated genes, such as the IL-7 receptor (Ilr7) (Gregory et al, 2007), tumor necrosis factor receptor superfamily 12, TNFRSF12/DR3 (Pappu et al, 2008) and TNF alpha induced protein 3 (TNFAIP3) (Prahalad et al, 2009) are known to confer susceptibility to multiple sclerosis. In addition, other candidates, such as chitinase-3-like (Chi3 l) (Canto et al, 2012;Comabella et al, 2010) and soluble TLR-4 co-receptor, sCD14 (Brettschneider et al, 2002) have been evaluated as biomarkers for MS, suggesting that R-flurbiprofen regulated several genes which are important in the human disease. Importantly, R-flurbiprofen per se did not affect gene expression in CFA control mice, which would be indicative of immunosuppressive effects but apparently, it blocks the activation process both of microglia/macrophages and of T cells and may help to maintain immune tolerance.…”
Section: Embo Molecular Medicinementioning
confidence: 99%